The effect of Aspergillus niger extract on the tissues of mung seedlings (Journal of the College of Basic Education, 2023)
A study was conducted on the effect of Aspergillus niger fungus filtrate on the seeds of Vigna radiata (L.) Wilczer, where the seeds were soaked in the fungus filtrate for eight hours, then microscopic hand sections were taken to study the detection of tissues in the root, subcotyledon peduncle and cotyledons in the germinated seeds. The results showed that the filtrate caused a decrease in the percentage of germination in the treated seeds, in addition to stunting the growth of the roots and the subcotyledonous peduncle. Microscopic sections in the subcotyledon stalk of germinated seeds showed an increase in the number of epidermal appendages, a disorder in the organization and arrangement of the barnacle cells of the cortex, a difference in their sizes, and changes in the vacuoles of the inner cortex cells, forming a continuous vacuole ring around the vascular cylinder, as well as the occurrence of dispersion and disappearance in some wood vessels. In the transverse sections of the two cotyledons in the treated seeds, starch grains appeared and were scattered in most of the parenchymal cells, while in the untreated seeds, they disappeared from the parenchymal cells except for the cells surrounding the vascular bundles, and no changes appeared in the pulp.